PERBEDAAN HEMODINAMIK ANTARA PASIEN SPINAL ANESTESI DENGAN SADDLE BLOCK ANESTESI PADA SAAT INTRA ANESTESI DI RUMAH SAKIT KARTIKA HUSADA TK II PONTIANAK KALIMANTAN BARAT - Ismail; Martyarini Budi; Indri Heri Susanti (Jurnal Cakrawala Ilmiah, 2023)
: Spinal Anesthesia or subarachnoid block (SAB) is a regional anesthetic technique that is performed by injecting local anesthetic drugs into the subarachnoid space to obtain analgesia at a certain dermatome level and relaxation of skeletal muscles. Meanwhile, saddle block is a type of low spinal block that manifests anesthesia in the saddle area, namely the perineum, perianal area, and medial aspect of the legs, and thighs. The anesthetic action causes hemodynamic changes, namely blood pressure, pulse, respiration, oxygen saturation and mean atrial pressure. This study purposes to analyze the hemodynamic comparison between Spinal Anesthesia and Saddle Block Anesthesia patients during surgery. This research method is quantitative research with an analytic descriptive method. The subjects of this study were patients who underwent saddle block anesthesia and spinal anesthesia procedures. The research data taken in this study were secondary data from medical record history for 3 months, amounting to 50 respondents for each cases. Statistical test results on all hemodynamic variables including systolic blood pressure, diastolic blood pressure, respiratory rate, heart rate, oxygen saturation, and mean atrial pressure showed a p-value of less than 0.05 (p-value <0.05) concluded that there is a difference in hemodynamics between patients performed spinal anesthesia and saddle block anesthesia during anesthesia